MODERN METHODS OF TEACHING RUSSIAN LANGUAGE - Khakimova Nasiba Turgunovna (American Journals, 2023)
The current stage of development of society poses a number of fundamentally new problems for the education system due to political, socio-economic, ideological and other factors, among which the need to improve the quality and accessibility of education should be highlighted. Increasing academic mobility, integration into the global scientific and educational space, creating economically optimal educational systems, increasing the level of university corporatism and strengthening ties between different levels of education. Innovation means innovation, novelty, change; innovation as a means and process involves the introduction of something new. In relation to the pedagogical process, innovation means the introduction of something new into the goals, content, methods and forms of teaching and upbringing, the organization of joint activities of the teacher and the student. This article examines some types of modern innovative technologies. Innovative technology develops day by day and poses great challenges to us that can be solved in the course of teaching students. Modern technology opens up new perspectives for language learning and unlocks the potential of students.
Keywords: innovation, information technology, multimedia, electronic portfolio.